(untitled) (KYAMC Journal, 2020)
Background: Cortical mastoidectomy with tympanoplasty is considered the standard of treatment in case of active mucosal chronic otitis media, refractory to medical treatment. Objective: Aim for this study was to find out the efficacy of cortical mastoidectomy with tympanoplasty in the management of chronic mucosal otitis media. Materials and Methods: This is an observational study conducted from January 2016 to July 2016. Total 50 patients were included in this study. Inclusion criteria was diagnosed cases of mucosal chronic otitis media with persistent ear discharge, adequate medical treatment, age between 15-60 years of both sexes. All the patients underwent cortical mastoidectomy with tympanoplasty, and patients were followed up to 12 weeks to evaluate graft take rate and compare pre-operative and post-operative hearing status. Results: In this study male to female ratio was 1.17:1. Mean age of study group was 30.66 ( 9.62) years. Graft uptake was successful in 43 (87%) and in 07 (14%) graft didn’t take. Graft take rate was highest in 15-30 years age group. Mean preoperative and post-operative air bone gap were 28.45 (7.69) dB and 25.30 ( 8.5) dB respectively. Conclusion: Cortical mastoidectomy with tympanoplasty shows good outcome in aspects of disease clearance and graft uptake success in chronic mucosal otitis media. Although hearing gain occurs in most cases, it is rather modest. KYAMC Journal Vol. 11, No.-2, July 2020, Page 91-95